Faecal microbiota transplantation for first or second Clostridioides difficile infection (EarlyFMT): a randomised, double-blind, placebo-controlled trial. (December 2022) - Baunwall, Simon Mark Dahl; Andreasen, Sara Ellegaard; Hansen, Mette Mejlby; Kelsen, Jens; Høyer, Katrine Lundby; Rågård, Nina; Eriksen, Lotte Lindgreen; Støy, Sidsel; Rubak, Tone; Damsgaard, Else Marie Skjøde; Mikkelsen, Susan; Erikstrup, Christian; et al.
Summary: Background: Clostridioides difficile infection is an urgent antibiotic-associated health threat with few treatment options. Microbiota restoration with faecal microbiota transplantation is an effective treatment option for patients with multiple recurring episodes of C difficile . We compared the efficacy and safety of faecal microbiota transplantation compared with placebo after vancomycin for first or second C difficile infection. Methods: We did a randomised, double-blind, placebo-controlled trial (EarlyFMT) at a university hospital in Aarhus, Denmark. Eligible patients were aged 18 years or older with first or second C difficile infection (defined as ≥3 watery stools [Bristol stool chart score 6–7] per day and a positive C difficile PCR test). Patients were randomly assigned (1:1) to faecal microbiota transplantation or placebo administered on day 1 and between day 3 and 7, after they had received 125 mg oral vancomycin four times daily for 10 days. Randomisation was done by investigators using a computer-generated randomisation list provided by independent staff. Patients and investigators were masked to the treatment group. The primary endpoint was resolution of C difficile -associated diarrhoea (CDAD) 8 weeks after treatment. We followed up patients for 8 weeks or until recurrence. We planned to enrol 84 patients with a prespecified interim analysis after 42 patients. The primary outcome and safety outcomes were analysed in the intention-to-treat population, which included all randomly assigned patients. The trial is registered with ClinicalTrials.gov, NCT04885946 . Findings: Between June 21, 2021, and April 1, 2022, we consecutively screened 86 patients, of whom 42 were randomly assigned to faecal microbiota transplantation (n=21) or placebo (n=21). The trial was stopped after the interim analysis done on April 7, 2022 for ethical reasons because a significantly lower rate of resolution was identified in the placebo group compared with the faecal microbiota transplantation group (Haybittle-Peto boundary limit p<0·001). 19 (90%; 95% CI 70–99) of 21 patients in the faecal microbiota transplantation group and seven (33%, 95% CI 15–57) of 21 patients in the placebo group had resolution of CDAD at week 8 (p=0·0003). The absolute risk reduction was 57% (95% CI 33–81). Overall, 204 adverse events occurred, with one or more adverse events being reported in 20 of 21 patients in the faecal microbiota transplantation group and all 21 patients in the placebo group. Diarrhoea (n=23 in the faecal microbiota transplantation group; n=14 in the placebo group) and abdominal pain (n=14 in the faecal microbiota transplantation group; n=11 in the placebo group) were the most common adverse events. Three serious adverse events possibly related to study treatment occurred (n=1 in the faecal microbiota transplantation group; n=2 in the placebo group), but no deaths or colectomies during the 8-week follow-up. Interpretation: In patients with first or second C difficile infection, first-line faecal microbiota transplantation is highly effective and superior to the standard of care vancomycin alone in achieving sustained resolution from C difficile . Funding: Innovation Fund Denmark.